LANGUAGE OF POWER AND PUBLIC RESISTANCE: A CRITICAL DISCOURSE ANALYSIS OF GORONTALO MAYOR’S POPULIST RHETORIC ON STREET VENDING POLICY - Moh Adriansyah Lahamu; Mohamad Akmal; Lisnawati Mahajia; Salma Djafar; Rahman Taufiqrianto Dako; Adriansyah Abu Katili (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
The phenomenon of populist rhetoric in Indonesian local politics demonstrates the paradox between moral empathy and violation of the rule of law. This research focuses on the case of Gorontalo Mayor Adhan Dambea, who openly encouraged MSMEs to sell on the sidewalk under the pretext of siding with the common people. His statement — “Kami berpihak pada rakyat, bukan pejabat. Kalau ada yang melarang, saya pasang badan.” — sparked a public debate that represented a discursive battle between moral legitimacy and legal norms. This research uses an approachqualitative-descriptivewith the methodCritical Discourse Analysis (Fairclough) combined with theorypopulism, through the modelEmpirical dual-layer CDA:simultaneous analysis of (1) the leader's discourse (institutional discourse) and (2) public counter-discourse. Data was obtained from the Mayor's statements in online media ( Pikiran Rakyat, RRI Gorontalo, Gorontalo Post, Website Pemkot ) and public comments on TikTok and news columns. The research results show three main findings: (1) populist rhetoric operates through moral empathy as legitimation for rule violations, (2) legal ambiguity is exploited as a source of symbolic power to frame moral actions, and (3) public counter-discourse forms moral resistance that affirms the supremacy of law and pedestrian rights. Theoretically, this study extends Fairclough's model by adding a dimension-populist empathy as a form of discursive power, and demonstrates that local political language plays an active role in shaping spatial planning and social legitimacy. The results are expected to form the basis for empathetic, legal, and just public communication.Keywords: Populist rhetoric, Critical Discourse Analysis, moral empathy, legal legitimacy, public counter-discourse, Gorontalo City